Thermal Process Time and Sensory Evaluation for Canned Cactus Pear Nectar - El-Samahy, S.K.; El-Mansy, H.A.; Bahlol, H.E.; El-Desouky, A.I.; Ahmed, A.E. (Journal of the Professional Association for Cactus Development, 2008)
Cactus pear fruits have high nutritional value due to their high amounts of sugar and minerals. Cactus pear fruits were peeled and pulped in a pulping machine. The strained pulp was used to prepare cactus pear pulp and nectar. The obtained cactus pear pulp was used to produce canned cactus pear nectar, which was used to determine the heat resistance parameters of pectin methylesterase. The obtained D and Z values, = 1.85 min, were used to evaluate the thermal process of canned cactus pear nectar. Heating penetration curves for heating and cooling processes were calculated. Chemical properties and sensory characteristics of canned cactus pear nectar were determined.